E‐plane probe microstrip to waveguide transition with fin‐line back‐short structure for millimetre‐wave application. Issue 23 (1st November 2017) - Xu, Zhengbin; Xu, Jie; Cui, Yinjie; Juo, Jian; Qian, Cheng
Abstract : A novel E ‐plane probe microstrip‐to‐waveguide transition for millimetre‐wave application is proposed. By introducing a fin‐line back‐short structure, tight‐tolerance machining and assembling of the waveguide back‐short commonly encountered with traditional E ‐plane probe microstrip‐to‐waveguide transition are no longer necessary. A Ka‐band transition prototype is designed and fabricated to validate the design concept. Simulated and measured results agree well and both of them show the proposed transition achieved good return and insertion losses over the full Ka band.